Hardware and software complex for stability control of quarry sides using optical fiber - Madi, P.Sh.; Al’kina, A.D.; Mekhtiyev, A.D.; Yurchenko, A.V. (Karagandy University of the name of acad. E.A. Buketov, 2024)
This article explores solutions to address the issue of implementing a shift monitoring system in quarries, which is the primary cause of collapsing sides and edges. For guaranteed safety and continuous monitoring of the quarry's activities, advanced fiber-optic sensors have been integrated. Their design is based on the use of single-mode optical fibers, which provides the most accurate assessment of displacements in mountainous terrain up to a distance of 30 km. Extensive laboratory studies have been carried out to deeply analyze the deformation and shear processes occurring in this geographical area. The results obtained from these analyses bode well for a significant improvement in quarry performance and a reduction in the likelihood of emergency situations.
Keywords: fiber-optic sensor; monitoring system; open-pit mining; quarry; safety; mining; optical fiber; deformation; shear